Functional characterization of α-Gal producing lactic acid bacteria with potential probiotic properties - Timothy Bamgbose; Pilar Alberdi; Isa O. Abdullahi; Helen I. Inabo; Mohammed Bello; Swati Sinha; Anupkumar R. Anvikar; Lourdes Mateos-Hernandez; Edgar Torres-Maravilla; Luis G. Bermúdez-Humarán; Alejandro Cabezas-Cruz; Jose de la Fuente (Scientific Reports, 2022)
Abstract The possibility of exploiting the human immune response to glycan α-Gal for the control of multiple infectious diseases has been the objective of recent investigations. In this field of research, the strain of Escherichia coli O86:B7 has been at the forefront, but this Gram-negative microorganism presents a safety concern and therefore cannot be considered as a probiotic. To address this challenge, this study explored the identification of novel lactic acid bacteria with a safe history of use, producing α-Gal and having probiotic potential. The lactic acid bacteria were isolated from different traditionally fermented foods (kununn-zaki, kindirmo, and pulque) and were screened for the production of α-Gal and some specific probiotic potential indicators. The results showed that Ten (10) out of forty (40) [25%] of the tested lactic acid bacteria (LAB) produced α-Gal and were identified as Limosilactobacillus fermentum, Levilactobacillus brevis, Agrilactobacillus composti, Lacticaseibacillus paracasei, Leuconostoc mesenteroides and Weissella confusa. Four (4) LAB strains with highest levels of α-Gal were further selected for in vivo study using a mouse model (α1,3GT KO mice) to elucidate the immunological response to α-Gal. The level of anti-α-Gal IgG observed were not significant while the level of anti-α-Gal IgM was lower in comparison to the level elicited by E. coli O86:B7. We concluded that the lactic acid bacteria in this study producing α-Gal have potential probiotic capacity and can be further explored in α-Gal-focused research for both the prevention and treatment of various infectious diseases and probiotic development.